2005
DOI: 10.1093/gerona/60.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Peak Aerobic Power, Left Ventricular Morphology, and Muscle Strength in Healthy Older Women

Abstract: The effect that aerobic (AT) and/or strength training (ST) has on altering peak aerobic power (VO2peak), muscle strength, left ventricular (LV) morphology, and diastolic filling in healthy older women is not known. We assessed the effects of 12 weeks of AT, ST, combined aerobic and strength training (COMT), or no training (NT) on VO2peak, muscle strength, LV morphology, and diastolic filling in 31 healthy women (68 +/- 4 years). Relative VO2peak was significantly greater after 12 weeks of AT, ST, or COMT. Uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 40 publications
1
44
1
Order By: Relevance
“…Most studies included both men and women, although 10 trials included men only (Fatouros 2002; Hagerman 2000; Haykowsky 2000; Hepple 1997; Izquierdo 2004; Katznelson 2006; Kongsgaard 2004; Maiorana 1997; Segal 2003; Sousa 2005) and 22 trials included women only (Bean 2004; Brochu 2002; Charette 1991; Damush 1999; Fahlman 2002; Flynn 1999; Frontera 2003; Haykowsky 2005; Jones 1994; Kallinen 2002; Liu-Ambrose 2005; Macaluso 2003; Madden 2006; Nelson 1994; Nichols 1993; Parkhouse 2000; Pu 2001; Rhodes 2000; Sipila 1996; Skelton 1995; Skelton 1996; Taaffe 1996). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies included both men and women, although 10 trials included men only (Fatouros 2002; Hagerman 2000; Haykowsky 2000; Hepple 1997; Izquierdo 2004; Katznelson 2006; Kongsgaard 2004; Maiorana 1997; Segal 2003; Sousa 2005) and 22 trials included women only (Bean 2004; Brochu 2002; Charette 1991; Damush 1999; Fahlman 2002; Flynn 1999; Frontera 2003; Haykowsky 2005; Jones 1994; Kallinen 2002; Liu-Ambrose 2005; Macaluso 2003; Madden 2006; Nelson 1994; Nichols 1993; Parkhouse 2000; Pu 2001; Rhodes 2000; Sipila 1996; Skelton 1995; Skelton 1996; Taaffe 1996). …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight trials had three groups. Among these trials, 14 included an aerobic training group in addition to a PRT group and a control group (Ettinger 1997; Fahlman 2002; Fatouros 2002; Haykowsky 2005; Hiatt 1994; Jubrias 2001; Kallinen 2002; Madden 2006; Malliou 2003; Mangione 2005; Pollock 1991; Sipila 1996; Topp 2005; Wood 2001), and seven included two PRT groups that exercised at different intensities in addition to a control group (de Vos 2005; Fatouros 2005; Hortobagyi 2001; Hunter 2001; Kalapotharakos 2005; Seynnes 2004; Singh 2005). One trial had a PRT group, a functional training group, and a PRT with functional training group (Manini 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance exercise training (EET) in older individuals can partially restore this age-mediated decline in V O 2max by favorable improvements in left ventricular (LV) function, myocardial blood flow distribution, and skeletal muscle oxidative capacity and function (19). Recent evidence suggests that gender plays a significant role in these physiological adaptations; older women adapt mostly by increasing arteriovenous O 2 differences, whereas in older men a large portion of the traininginduced gain in V O 2max is attributable to higher cardiac output and stroke volume during maximal exercise (14,45,46).…”
mentioning
confidence: 99%
“…Moreover, it is suggested that 1 RM BP contributes to the rate of force development of the power exertion using SSC. Training not only athletes but also reinforcing muscle power as part of a senior citizen's health measures is attracting attention, and research on the muscle power evaluation of the senior citizen has advanced in recent years (Symons et al, 2004;Haykowsky et al, 2005). The finding concerning muscle power that uses SSC will contribute to the training regime of senior citizens in the future.…”
Section: Relationships Between the Muscle Power Parameters And A One-mentioning
confidence: 99%